Employees’ Responses to Teamwork: A Taxonomy in Relation to the Change Process - Silva, M. Gabriela (14th EURAM 2014, 2014)
This paper examines how employees make sense and shape management-initiated workplace changes. Taking as the starting point the inconsistent findings of existing research into teamwork and arguing for a perspective that starts with an understanding of the microscopic struggles with management in the context of established hierarchical relationships, a new typology of employees’ responses to teamwork is developed. It is argued that greater coherence and integration of the social and interactive aspects of the organization of work is achieved by defining, sorting, and searching employees’ perceptions and responses according to four categories: prudent conformism, conservative resistance, political mobilization, and entrepreneurial alliance. This paper concludes with a brief discussion of implications for theory and practice.